Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/molecules25040964
|View full text |Cite
|
Sign up to set email alerts
|

Bersavine: A Novel Bisbenzylisoquinoline Alkaloid with Cytotoxic, Antiproliferative and Apoptosis-Inducing Effects on Human Leukemic Cells

Abstract: Bersavine is the new bisbenzylisoquinoline alkaloid isolated from the Berberis vulgaris L. (Berberidaceae) plant. The results of cytotoxicity screening 48 h post-treatment showed that bersavine considerably inhibits the proliferation and viability of leukemic (Jurkat, MOLT-4), colon (HT-29), cervix (HeLa) and breast (MCF-7) cancer cells with IC50 values ranging from 8.1 to 11 µM. The viability and proliferation of leukemic Jurkat and MOLT-4 cells were decreased after bersavine treatment in a time- and dose-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Another study showed weak anti-microbial activity against Plasmodium falciparum with low cytotoxicity in the KB cell line 42 . Although there is little published research on aromoline, various bisbenzylisoquinoline alkaloids are being studied for their anti-proliferative, anti-inflammatory and anti-microbial properties [43][44][45][46][47][48] . This is the first study to our knowledge that explores the effects of aromoline on chondrocytes and chondrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed weak anti-microbial activity against Plasmodium falciparum with low cytotoxicity in the KB cell line 42 . Although there is little published research on aromoline, various bisbenzylisoquinoline alkaloids are being studied for their anti-proliferative, anti-inflammatory and anti-microbial properties [43][44][45][46][47][48] . This is the first study to our knowledge that explores the effects of aromoline on chondrocytes and chondrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity was observed against all tested cell lines, with IC 50 values ranging from 245 to 473 μg/mL. Bersavine, a bisbenzylisoquinoline alkaloid isolated from Berberis vulgaris, inhibits the proliferation and viability of leukemic (Jurkat, MOLT-4), colon (HT-29), cervix (HeLa), and breast (MCF-7) cancer cells, with IC 50 values ranging from 8.1 to 11 μM [ 12 ]. A relatively low cytotoxicity (compared to doxorubicin) was reported for Berberis integerrima leaves extract against breast cancer (MCF-7), epidermal (A431), and glioma (U87-MG) cell lines [ 13 ].…”
Section: Introductionmentioning
confidence: 99%